Respuesta :
[tex] \left\{\begin{array}{ccc}y=x-1\\y=2x+1\end{array}\right\Rightarrow 2x+1=x-1\\\\2x+1=x-1\ \ \ \ |-1\\2x=x-2\ \ \ |-x\\x=-2\\\\\text{substitute the value of x to the first equation}\\\\y=-2-1\\y=-3\\\\\text{Answer:}\ \boxed{x=-2;\ y=-3} [/tex]
Since the equations are equal to each other, let's set them up.
x-1=2x+1; let's add 1 to both sides.
x=2x+2; let's subtract 2x from both sides.
-x=2; we need x to be positive so let's divide it by -1.
x=-2
Let's see what y is and see if x is -2.
y=-2-1=-3
y=-2(-2)+1=-4+1=-3
So, x=-2 and y=-3.